Hunting a light U(1)B gauge boson coupled to baryon number in collider experiments - Drees, M. [UNESP]; Éboli, O. J P [UNESP]; Mizukoshi, J. K. (Elsevier, 1999)
We analyze several signals at HERA and the Tevatron of a light U(1)B gauge boson (γB) coupling to baryon number. We show that the study of the production of bb pairs at the (upgraded) Tevatron can exclude γB with masses (mB) in the range 40 ≲ mB ≲ 300 GeV for γB couplings (αB) greater than 2 × 10-2 (3 × 10-3). We also show that the HERA experiments cannot improve the present bounds on γB. Moreover, we demonstrate that the production at HERA and the Tevatron of di-jet events with large rapidity gaps between the jets cannot be explained by the existence of a light γB. © 1999 Published by Elsevier Science B.V. All rights reserved.